2018
DOI: 10.1111/jopy.12396
|View full text |Cite
|
Sign up to set email alerts
|

Eyebrows cue grandiose narcissism

Abstract: Together, these data show that distinctive eyebrows reveal narcissists' personality to others, providing a basic understanding of the mechanism through which people can identify narcissistic personality traits with potential application to daily life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Using a new set of stimuli, our analyses indicated that high narcissism was the only dark triad trait that could be detected in both female and male prototypes. These results replicate Holtzman's (2011) results for narcissism and are also consistent with other recent work suggesting the existence of facial correlates of narcissism (Giacomin & Rule, 2018). Participants did not identify high-Machiavellianism female or male prototypes and detected highpsychopathy female prototypes correctly less often than would be expected by chance alone.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Using a new set of stimuli, our analyses indicated that high narcissism was the only dark triad trait that could be detected in both female and male prototypes. These results replicate Holtzman's (2011) results for narcissism and are also consistent with other recent work suggesting the existence of facial correlates of narcissism (Giacomin & Rule, 2018). Participants did not identify high-Machiavellianism female or male prototypes and detected highpsychopathy female prototypes correctly less often than would be expected by chance alone.…”
Section: Discussionsupporting
confidence: 90%
“…Future studies should also investigate if participants who score higher on the dark triad can more easily detect dark triad traits in faces, since women who scored higher on Machiavellianism have been found to be better at detecting lies (Lyons et al, 2017). Additionally, it may be important to explore which facial features are related to high dark triad traits, since a recent study found people can detect grandiose narcissism based on thickness and density of targets' eyebrows (Giacomin & Rule, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that unmeasured personality features (e.g., sociosexuality, self-rated attractiveness) of the raters may moderate these findings. Indeed, recent work suggests that eyebrows may signal personality qualities (e.g., narcissism; Giacomin and Rule, 2018) that influence perceptions of attractiveness. Additionally, effect sizes in the current study were relatively small, and so investigation into the mediating effects of individual difference variables may further explain this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…People can accurately perceive grandiose narcissism in others based on minimal information (e.g., Giacomin & Rule, 2018;Holtzman, 2011;Holtzman & Strube, 2013;Naumann, Vazire, Rentfrow, & Gosling, 2009;Vazire, Naumann, Rentfrow, & Gosling, 2008). They use cues associated with grandiose narcissists' physical appearance-such as stylish, expensive clothing and neater, more organized appearance (Back, Schmukle, & Egloff, 2010;Vazire et al, 2008)-to accurately perceive narcissism in others, yet still form positive first impressions of grandiose narcissists.…”
Section: Introductionmentioning
confidence: 99%